Peran Sinyal Keuangan pada Anggaran Pendapatan dan Belanja Daerah terhadap Kinerja Pemerintah Daerah - Prasetiyo, Yudhi; Zuhroh, Shufia; Nugraheni, Novita (E-Jurnal Akuntansi; Vol 33 No 4 (2023), 2023)
This research aims to allocate the APBD made and planned by the Regional Government to improve the performance of the Regional Government, especially in terms of regional welfare and development. The research population is 34 provinces in Indonesia in 2019-2021. This study uses several independent variables, namely regional wealth, regional size, and capital spending to examine the relationship between the dependency variables proxied by local government performance. The study used quantitative methods with multiple regression analysis using the IBM SPSS 25 statistical test tool. The results showed that regional wealth, regional size, and spending capital had no effect on regional government performance. Keywords: APBD; Local Government Financial Performance; Regional Wealth; Local Goverment Size; Capital Expenditures